Alcohol consumption among youth of Suryabinayak municipality, Bhaktapur. - Magar,Kripa Thapa (2016)
ABSTRACT: Background: Alcohol is the most commonly used and abused drug among youth. Also, early initiation of alcohol use (before 14 years of age) is a predictor of impaired health status. It's not only that young people are drinking but the way they drink that puts them at such high risk for alcohol-related problems. I assessed the prevalence, factors associated with the alcohol use, pattern, frequency, context of alcohol consumption, health risk behavior and knowledge of youth on effects of alcohol consumption among the youth of Suryabinayak Municipality. Methods: A cross-sectional descriptive study using a modified standard questionnaire was conducted among 250 youth of Suryabinayak Municipality, Bhaktapur. Data was objectively analyzed in SPSS full version 23. Chi-square test and fisher's exact test was applied to examine the association between alcohol consumption and other variables. Results: Overall, 56% of youth reported current drinking, with male (37.6%) outnumbering female (18.4%). 32.8% of youth were lifetime abstainers while 73.6% of current drinkers were found to drink in the past 30 days. The mean age of initiating drinking alcohol was found to be 17 years. 61.9% were introduced into the alcohol by their friends. Almost half of the respondents (44.7%) drink beer. Female usually drink jaad/chyang, beer and wine whereas male usually drink jaad/chyang, beer, distillery products and mix. Among those who drink in past 30 days, 49.5% reported binge drinking (male 47.6%, female 1.9%). Female drink mostly at home (19.3%) and party (16.4%), while male mostly drink at friend's house (32.1%) and Bar/restaurant/hotel (30.7%). Male (61.4%) usually drink alcohol with their friends and female (19.3%) with their family members. Association of alcohol consumption was found to be highly significant with age group , gender, ethnicity, educational level, family history of alcohol use & friend_s history (p = <0.0001 at CI 95%). Conclusion: This study reports the prevalence of drinking alcohol among youth thrice that of the national figure. Majority of the youth was found to start drinking before the legal drinking age. Effective intervention strategies addressing the underage drinking need a great focus from community level to center level to prevent underage alcohol consumption. Key words: Alcohol consumption; Current drinkers; Suryabinayak Municipality; Youth.